2016
DOI: 10.1007/s00467-016-3317-5
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to define acute kidney injury in term newborns with hypoxic ischemic encephalopathy

Abstract: Background Current definitions of acute kidney injury (AKI) are not sufficiently sensitive to identify all newborns with AKI during the first week of life. Methods To determine whether the rate of decline of serum creatinine (SCr) during the first week of life can be used to identify newborns with AKI, we reviewed the medical records of 106 term neonates at risk of AKI who were treated with hypothermia for hypoxic ischemic encephalopathy (HIE). Results Of the newborns enrolled in the study, 69 % showed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 40 publications
(74 reference statements)
3
63
0
5
Order By: Relevance
“…SCr was measured once in four of 113 (3.5%), twice in six of 113 (5.3%), three times in ten of 113 (8.8%), and at least four times in 93 of 113 (82%) of the cohort during the 2 weeks of life (median, 5 [range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] days). Neonatal AKI was defined using the Kidney Disease Improving Global Outcomes AKI definition, in which stage 1 was defined as an increase of SCr $ 0.3 mg/dl or Figure 1.…”
Section: Definition Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…SCr was measured once in four of 113 (3.5%), twice in six of 113 (5.3%), three times in ten of 113 (8.8%), and at least four times in 93 of 113 (82%) of the cohort during the 2 weeks of life (median, 5 [range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] days). Neonatal AKI was defined using the Kidney Disease Improving Global Outcomes AKI definition, in which stage 1 was defined as an increase of SCr $ 0.3 mg/dl or Figure 1.…”
Section: Definition Of Outcomesmentioning
confidence: 99%
“…Prior literature has shown that in premature infants without AKI, urine proteins will be highest among those with the lowest GA, probably because of the passive loss of proteins in the context of immature tubular function (6)(7)(8). Previously, we (7) and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have published data on the ability of urine biomarkers to predict AKI in neonates; however, these studies are limited by the size of the cohort or the use of nested case-control methods, with most of these studies evaluating only one biomarker. In addition, previous studies were subject to risk of misclassification bias, given that many infants had only a few SCr levels measured to determine AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Частота ураження нирок при перинатальній асфіксіі становить 65-70%. Зни жена перфузія ниркових судин особливо пошкоджує проксимальні канальні [10,14] та веде до розвитку гострого тубулярного некрозу, і як наслідок, до гострої ниркової недостатності [22]. Такі патологічні прояви підвищують ризик патології нирок і в подаль шому житті [2,3].…”
Section: вступunclassified
“…Serum creatinine will not begin to rise until 25 to 50% of renal function is lost, thus significant injury can occur without changes in creatinine [92]. The change in serum creatinine levels over the first few days is predictive of renal injury, with normal values of >50% decline or serum creatinine <0.6 is found in 70% of infants after HIE [93]. A fractional excretion of sodium of greater than 3% is moderately specific after 48 hours for AKI [84].…”
Section: Renal Dysfunction and Electrolyte Disturbances After Birth Amentioning
confidence: 99%
“…A fractional excretion of sodium of greater than 3% is moderately specific after 48 hours for AKI [84]. Although Cystatin C (CysC) and neutrophil gelatinase-associated lipocalin (NGAL) are both specific markers of other pediatric kidney injury, they can be elevated by birth asphyxia and unable to determine whether an infant will develop AKI [93, 94]. A recent study demonstrated a NGAL level greater than 250 ng/ml was significantly associated with severe HIE and mortality [95].…”
Section: Renal Dysfunction and Electrolyte Disturbances After Birth Amentioning
confidence: 99%